Next steps in development - below the neck stuff - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
This chapter explores how an effective development pathway builds and exploits the GMA base discussed in Chapter 4. The necessity for a breath of activity during the early years of development is explored for both optimising future development and ensuring that the developing athlete is equipped with the skills and knowledge to move between different activities as they develop. The limitations of a premature and overly restrictive movement pathway are explored, and practical guidance and suggestions are given about how to facilitate this breath of involvement for young athletes is presented. Consideration is given throughout this section as to how this movement diet is influenced by, for example, growth spurts during adolescence and other psycho-physiological and maturation issues.